A Model for Bank Management Performance Appraisal with the Advanced Technologies Approach (Meta-Synthesis Method) - Ehsan Kiani Ghalehno; Habibollah Salarzehi; Bahareh Naseri; Abdolali Keshtegar (پژوهش‌های مدیریت عمومی)
AbstractThe knowledge about human capital as a driving force of economic development has increased in recent years (Rashki , 2019). "Industry 0. 4" or "Fourth Industrial Revolution" is changing our lifestyles and customer-bank relations. It inevitably interprets that both existing commercial techniques and monetary management are not excluded from this change (Singh , 2022). Rapid changes in today's world have created great challenges for banks. Pioneer banks took advantage of opportunities with managerial tools and advanced technologies to achieve banking objectives (Najafbeigi et al , 2011). Such measures lead to bank changes, discussion of the bank's problems, solving problems, and preparing the bank for a successful future.IntroductionAccording to reconstruction experts, if people are free to express their opinions and feelings, have peace of mind, and discuss conflicts freely, changes will be effectively made, leading to improvement in banking performance (Kamalian , 2013). Technology-based products create opportunities to have great cost advantages, increase profitability, and facilitate lower risk in comparison with traditional banking products. Additionally, electronic banking (services improve banking performance. Some less-developed and developing countries have not achieved the expected results because infrastructure investment is insufficient and customers prefer traditional branch-based banking (Akhisar , 2015). Banks make efforts to enhance their performance. Managers explicitly state that the current century needs greater productivity and efficiency than at any other time in history (Palma , 2017). The growth of knowledge and information technology security are increasing in developing countries because information and communication technology (ICT) plays a vital role in globalized economic scope. This is vastly accepted by a large number of banks, such as industrial companies, manufacturing companies, the health sector, the financial sector, and the educational system in their daily operations. The dynamics of events in the current competent financial world make financial banks dependent on this technology (Andry , 2017). The vast use of ICT helps financial institutions fulfill their customers' needs in different ways. Accordingly, banks widely utilize a variety of technological solutions such as central banking, mobile banking, e-banking, clearance of checks, and currency remittance. These emerging dynamic technologies are dangerous even if they have positive effects on financial institutions and bank managers cannot protect their information assets against any attack on information security (Okoht , 2020).Case studyAssessing the performance of managers in branches of melli Bank of Sistan and Baluchistan province.Materials and MethodsWe have great development in this space using IR 0. 4 as setting new records or applying for personal credits in advanced banks enables buyers to do banking operations using available strategic tools. Some open regional banks cause this computerized change to turn into an unknown level, but public regional banks are seeking to eliminate physical check cards, and thus there will be a few need to have plastic cards in the next 5 years (Lak , 2018). In today's banking industry, technology is the skill of manufacturing a product, which can be a service or software. Furthermore, advanced technology refers to skills that are newer regarding the implementation and utilization of infrastructures. Digital signatures, biometric authentication systems, and web service of electronic systems in the processes are among these advanced technologies in this industry. Given the importance of this scope, the present study sought to design a performance appraisal maturity model for bank managers based on the advanced technology approach. Therefore, a large number of management performance appraisal dimensions were evaluated using the advanced technology approach but no study provided a full model for management performance appraisal with the advanced technology approach. To this end, this research aimed to review previous studies and detect the determinants of management performance appraisal with the advanced technology approach. The models were studied, and finally, a comprehensive model was provided for the management performance appraisal with the advanced technology approach. The important question is what factors affect the bank management performance appraisal with the advanced technology approach?